2016
DOI: 10.5194/acp-16-5853-2016
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric changes caused by galactic cosmic rays over the period 1960–2010

Abstract: Abstract. The Specified Dynamics version of the Whole Atmosphere Community Climate Model (SD-WACCM) and the Goddard Space Flight Center two-dimensional (GSFC 2-D) models are used to investigate the effect of galactic cosmic rays (GCRs) on the atmosphere over the 1960-2010 time period. The Nowcast of Atmospheric Ionizing Radiation for Aviation Safety (NAIRAS) computation of the GCRcaused ionization rates are used in these simulations. GCRcaused maximum NO x increases of 4-15 % are computed in the Southern polar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 57 publications
4
42
0
1
Order By: Relevance
“…Energetic particles have the ability to produce odd nitrogen and odd hydrogen species, NO Dorman, 2004), so that they penetrate deep into the atmosphere. Their influence is largest in the polar lower stratosphere and upper troposphere (Calisto et al, 2011;Jackman et al, 2016;Mironova et al, 2015). Their intensity is anticorrelated with the solar activity (Bazilevskaya et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Energetic particles have the ability to produce odd nitrogen and odd hydrogen species, NO Dorman, 2004), so that they penetrate deep into the atmosphere. Their influence is largest in the polar lower stratosphere and upper troposphere (Calisto et al, 2011;Jackman et al, 2016;Mironova et al, 2015). Their intensity is anticorrelated with the solar activity (Bazilevskaya et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…The model has full stratospheric chemistry, and its computational efficiency makes it a very useful tool for performing numerous sensitivity tests. The model has undergone extensive improvement and evaluation over the years (e.g., Bacmeister et al, 1995;Considine et al, 1994;Fleming et al, 2007Fleming et al, , 2011Fleming et al, , 2015Jackman et al, 1996Jackman et al, , 2016Rosenfield et al, 1997Rosenfield et al, , 2002 and is shown to provide realistic ozone responses to chlorine perturbations. A model description and evaluation of the baseline simulation of CFC-11 and ozone is provided in Appendix A.…”
Section: Model Simulations and Scenariosmentioning
confidence: 99%
“…The influence of GCRs on atmospheric chemistry has been investigated in several model studies (Krivolutsky et al, 2002;Rozanov et al, 2012;Mironova et al, 2015;Jackman et al, 2016). GCR-induced ozone reductions of more than 10 % in the tropopause region and up to a few percent in the polar lower stratosphere have been reported.…”
Section: Galactic Cosmic Raysmentioning
confidence: 99%